Pengaruh Harga, Kualitas Produk, Kualitas Pelayanan Dan Promosi Media Sosial Terhadap Keputusan Pembelian Produk Kosmetik Wardah (Studi Kasus Mahasiswa Feb Universitas Islam Malang) - Erlista, Silfa; Priyono, Achmad Agus; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of price, product quality, service quality, and social media promotion on purchasing decisions of Wardah cosmetic products (a case study on students of the Faculty of Economics and Business, Islamic University of Malang). The research uses a quantitative approach with purposive sampling technique, involving 140 respondents who are active students from the 2021–2024 batch and have previously purchased Wardah cosmetic products. Data was collected through an online questionnaire distributed via Google Form and analyzed using instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results show that the variables of price and product quality do not have a significant effect on purchasing decisions. Meanwhile, service quality has a positive and significant influence on purchasing decisions. On the other hand, social media promotion does not show a significant influence on purchasing decisions. These findings indicate that although price and social media promotion are part of marketing strategies, good service plays a more vital role in influencing consumer purchasing decisions. Keywords: Price, Product Quality, Service Quality, Social Media Promotion And Purchasing Decision.